Effects of juniper essential oil on growth performance, some rumen protozoa, rumen fermentation and antioxidant blood enzyme parameters of growing Saanen kids. Issue 5 (16th October 2016) - Yesilbag, D.; Biricik, H.; Cetin, I.; Kara, C.; Meral, Y.; Cengiz, S. S.; Orman, A.; Udum, D.
Summary: This study aimed to evaluate the effects of juniper essential oil on the growth performance, rumen fermentation parameters, rumen protozoa population, blood antioxidant enzyme parameters and faecal content in growing Saanen kids. Thirty‐six male Saanen kids (36 ± 14 days of age) were used in the study. Each group consisted of 9 kids. The control group (G1) was fed with a diet that consisted of the above concentrated feed and oat hay, whereas the experimental groups consumed the same diet but with the concentrated feed uniformly sprayed with juniper essential oil 0.4 ml/kg (G2), 0.8 ml/kg (G3) or 2 ml/kg (G4). There were no differences (p > 0.05) in live weight, live weight gain or feed consumption between the control and experimental groups. There was a significant improvement (p < 0.05) in feed efficiency in the G3 group. There were no differences in the rumen pH, rumen volatile fatty acid (VFA) profile or faecal pH of the control and experimental groups. The rumen NH3 N values were similar at the middle and end of the experiment, but at the start of the experiment, the rumen NH3 N values differed between the control and experimental groups (p < 0.05). The faecal score value was significantly (p < 0.05) decreased in the experimental groups. The addition of juniper essential oil supplementation to the rations caused significant effects on the kids' antioxidant blood parameters. Although the superoxide dismutase (SOD) activity, total antioxidant capacity (TAC) and catalase values were significantly (p < 0.05) increased in the experimental groups (G2, G3 and G4), especially group G4, the blood glutathione peroxidase (GPX) value significantly decreased in the experimental groups. The results of this study suggest that supplementation of juniper oil is more effective on antioxidant parameters than on performance parameters and may be used as a natural antioxidant product.